Peningkatan Hasil Belajar Siswa Melalui Penggunaan Media English Vocabulary Card - Ahmad Halid; Vicky Fatimatus Zahra (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2021)
This article describes the urgency of using English Vocabulary Card media. Media cards contain pictures (objects, animals, and so on) that can train students and create vocabulary, these cards become instructions or stimuli for students to give good responses. The research problem is how is English Vocabulary Card media in improving class English learning outcomes?. The purpose of this research is to find out what the English Vocabulary Card media is in improving English learning outcomes for class V at MIMA 34 Hasyim Asy'ari, using a qualitative approach and statistical CAR analysis. The results showed that if the use of English Vocabulary Card media could improve student learning scores, it was seen from the results before using that students got a percentage of 42.8% after using the English Vocabulary Card media, student scores could increase by 92.8%. Keywords: Learning Outcomes, Media English Vocabulary Card